If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+(90-x)+(180-2x)=180
We move all terms to the left:
x+(90-x)+(180-2x)-(180)=0
We add all the numbers together, and all the variables
x+(-1x+90)+(-2x+180)-180=0
We get rid of parentheses
x-1x-2x+90+180-180=0
We add all the numbers together, and all the variables
-2x+90=0
We move all terms containing x to the left, all other terms to the right
-2x=-90
x=-90/-2
x=+45
| 8x+35=-45 | | x(x^2-3x+2)=6000 | | 6x-7+11=180 | | 14−3x=−-4x | | 3/4x-1/2=2/3x+5/6 | | 22=0a | | 0.4(15+6)=1.5(4p+1.6) | | 6÷n=-14 | | 3(7x-1)-2(6x)=24 | | 5-8x=32 | | 3+5x+4=4 | | -10v=-50 | | 4n-28=5n | | -x+3=35 | | 4.2^x=7.2^(2x) | | 6 | | 12/100*x=36600 | | (47-3x)/7=2x-3 | | -9=(3/4)x | | X-5(2x+7)=7-9x | | 14+16=-5(6x-6) | | 2x-8+x/17=39 | | -17+72=-5(x+4) | | −8/9=v−1/2 | | −89=v−21 | | 6(x+2)/5=4x-2 | | 6-3(4x+1)=15-10x | | 3y+7-7=5+2y+2 | | 10x+7=72 | | 6+18m=(-16m)-40-4 | | (8)(3)m=2 | | 6u^2-26u+20=0 |